Phylogenetic comparative analysis: Chemical and biological features of caseins (alpha-S-1, alpha-S-2, beta- and kappa-) in domestic dairy animals - Hassanin, Abdallah A.; Osman, Ali; Atallah, Osama Osman; El-Saadony, Mohamed T.; Abdelnour, Sameh A.; Taha, Heba S. A.; Awad, Mohamed F.; Elkashef, Hany; Ahmed, Ahmed Ezzat; Abd El-Rahim, Ibrahim; Mohamed, Abdullah; Eldomiaty, Ahmed S. (Frontiers in Veterinary Science, 2022)
Casein micelles determine the physicochemical, physiological and biological characteristics of the milk. Four casein micelles (alpha-S-1, alpha-S-2, beta and kappa) were Phylogenetically analyzed and in silico characterized regarding chemical, antimicrobial and antioxidant features in five dairy animals; Arabian camel, sheep, goat, cattle and water buffalo. The sequence of full-length amino acids of the four casein micelles for the five species was retracted from NCBI GenBank database. Multiple sequence alignment is used to further examine the candidate sequences for phylogenetic analysis using Clustal X and NJ-Plot tools. The results revealed that sheep and goat possess strong similarities (98.06%) because of their common ancestor. The same was observed with cattle and water buffalo (96.25%). The Arabian camel was located in a single subclade due to the low similarity in casein protein residues and compositions with other dairy animals. Protein modelling showed that alpha-S1- and alpha-S2-caseins possess the highest number of phosphoserine residues. The in silico computed chemical properties showed that β-casein recorded the highest hydrophobicity index and the lowest basic amino acids content while α-S2-casein showed the opposite. The computed biological parameters revealed that α-S2-casein presented the highest bactericidal stretches. Only Arabian camel β-casein and k-casein showed one bactericidal stretche. The analysis also revealed that β-casein particularly in Arabian camel possesses the highest antioxidant activity index. These results support importance of the bioinformatics resources to determine the chemical and biological activities of milk casein micelles.